Case Report: Triple-negative breast cancer with brain and meningeal metastases exhibits spatiotemporal heterogeneity in terms of HER2 expression - Wang, Xubin; Weng, Zhiyun (Frontiers in Oncology, 2025)
Meningeal carcinomatosis (MC) is a distinct form of brain metastasis (BM) that occurs in patients with advanced triple-negative breast cancer (TNBC). The occurrence of BM typically indicates a poor prognosis. Spatial heterogeneity in HER2 expression is relatively common in breast cancer cases; however, the emergence of both temporal and spatial heterogeneity within the brain parenchyma and cerebrospinal fluid (CSF) is exceedingly rare. Thus, the phenomenon warrants further investigation. Herein, we report a case of advanced TNBC with BM and MC. HER2 was expressed in the CSF and exhibited spatial and temporal heterogeneity. The CSF was analyzed using immunohistochemistry and flow cytometry, confirming the presence of HER2-positive tumor cells in the patient’s CSF. MC was effectively controlled after treatment with trastuzumab deruxtecan (T-DXd). Relevant literature was reviewed to analyze the reasons for this phenomenon. In this case, the spatial and temporal heterogeneity of the HER2 receptors observed in the CSF suggests that BM may be driven by the synergistic interaction of multiple subclonal tumor cells.